6-gingerol and its derivatives inhibit Helicobacter pylori-induced gastric mucosal inflammation and improve gastrin and somatostatin secretion - Qian, Jiali; Li, Zhennan; Wang, Jinhui; Lin, Yuxian; Yu, Yingcong (Frontiers in Microbiology, 2024)
Helicobacter pylori (H.pylori) resistance has increased in recent years, and research and development of new drugs become a trend. In our study, three derivatives (JF-1, JF-2, JF-3) were synthesized using 6-gingerol as the main component, while JF-4, containing both 6-gingerol and 6-shogaol as the main components, was extracted from dried ginger. The MICs, determined by the ratio dilution method, were 80 µg/mL for JF-1, 40 µg/mL for JF-2, 30 µg/mL for JF-3, 40 µg/mL for JF-4, 60 µg/mL for 6-gingerol standard (SS), and 0.03 µg/mL for amoxicillin (AMX). After treating H. pylori-infected mice, the inflammation of the gastric mucosa was suppressed. The H. pylori eradication rate was 16.7% of JF-3 low-dose treatment (LDT), 25.0% of JF-3 high-dose treatment (HDT), 16.7% of JF-4 LDT, 16.7% of JF-4 HDT, 30% of SS LDT, 50% of SS HDT, and 36.4% of positive control group(PCG), respectively. The levels of gastrin, somatostatin, were significantly recovered in the JF-3 and JF-4 administration groups, and the effect was stronger in the high-dose group. These results demonstrated that 6-gingerol and its derivatives had significant anti-Helicobacter pylori effects and were promising potential treatments for H.pylori infection.